Analisis Pilihan (Preferensi) Masyarakat Terhadap Permintaan Helm Di Kota Pekanbaru - Nursani Pulungan; Azwar Harahap; Sri Endang Kornita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to analize the demand that caused by several variables that tastet of consumers with quality, motive (style), colors, shapes, and price of the goods themselves. The study uses qualitative descriftive analysis answer get through questions naries with 100 sampels. From the research that has been done, it can be seen that the influence the choice of (prerence) communities to demand quality helmet is 24%, the price of 26%, the color by 15%, 12% shapes, while the motive (style) amounting to 23%. The servey results revealed that the helmets are more preferred by the respondent (the consumers) is a brand of GM is helmet. Then not that the price of much more desirable ranges from Rp 120,000 to Rp 154,000. While the most dominant factor that affect the choice of (preference) society to demand a helmet that is the price of the goods themselves.Keywords : Choice (Preference) Demand Helmet.